2011
DOI: 10.1111/j.1365-3164.2011.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone therapy for atopic dermatitis is less effective in dogs with lower pretreatment serum 25‐hydroxyvitamin D concentrations

Abstract: Serum 25-hydroxyvitamin D [25(OH)D] concentrations were measured in 20 dogs with atopic dermatitis prior to treatment with a standard therapeutic dosage of prednisolone (0.93-1.06 mg/kg) every other day for 5 weeks after 7 days of treatment with the same dosage once daily. The severity of their physical signs was scored before and 6 weeks after prednisolone treatment by the canine atopic dermatitis extent and severity index version 3 (CADESI-03) and the Edinburgh Pruritus Scale (EPS). The 20 dogs with atopic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
(107 reference statements)
3
15
0
Order By: Relevance
“…In addition it has been shown that low vitamin D status is associated with a poorer response to prednisolone treatment for canine atopic skin disease (Kovalik et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition it has been shown that low vitamin D status is associated with a poorer response to prednisolone treatment for canine atopic skin disease (Kovalik et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that low serum concentrations 25(OH)D are associated with an increased risk of 30 day mortality in sick cats (Titmarsh et al 2015). In addition it has been shown that low vitamin D status is associated with a poorer response to prednisolone treatment for canine atopic skin disease (Kovalik et al 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the growth of canine mast cell tumours is inhibited by vitamin D, and Labrador retriever dogs with low vitamin D levels have an increased risk in developing mast cell tumours . It is tempting to speculate that vitamin D may play a role in other mast cell‐related diseases, including AD, and in one study lower serum vitamin D levels were associated with a suboptimal response to prednisolone therapy . However, it is important to note that vitamin D levels did not correlate with the presence or severity of disease but only with the response to therapy.…”
Section: The Role Of Nutrition and Vitamins In The Pathogenesis Of Camentioning
confidence: 97%
“…with or without detectable allergen‐specific IgE) . In some dogs, the diagnosis of AD was made based upon clinical signs alone; in others, the method of diagnosis (specifically, whether the presence of allergen‐specific IgE was determined directly in serum or indirectly via IDT) was not mentioned or was unclear . On the face of it, such distinctions seem to matter little, because AD is generally considered to be a clinical diagnosis in dogs (largely because of the variabilities in IgE reactivity discussed above).…”
Section: Update On the Role Of Antibodies In Atopic Dermatitismentioning
confidence: 99%